Proyecto de factibilidad para la producción y comercialización de gomitas de colágeno a base de escamas de pescado en la ciudad de Loja. - Romero Guazha, Nataly Fernanda (2024)
The main objective of the research is to determine the feasibility for the production and commercialization of collagen gummies based on fish scale in the city of Loja, providing significant information that will allow making decisions to know if the project is economically and financially feasible. For which it was necessary to focus on a quantitative and qualitative research, with an exploratory, descriptive research level; in addition, the deductiv and inductive method was used, followed by techniques such as bibliographic compilation, interviews and surveys. With the results of the pilot plan, a sample of 164 surveys was established. The results showed an unsatisfied demand of 875,828 bottles of collagen gummies. The technical study showed a capacity utilization of 7,488 jars (year 1). The company will be located in the Borja neighborhood and will be incorporated as a Simplified Joint Stock Company (SAS). The financial study determined an investment of US$13,514.80, which will be financed with equity (65%) and a loan from Banco de Loja. The selling price of the product is $12.00 dollars per bottle (year 1). In the financial evaluation, the feasibility of the project was demonstrated with indicators such as: NPV amounts to $21. 228.98 dollars; the IRR is 78.97%, exceeding the minimum acceptable rate of return 20.90%; the benefit-cost ratio is $0.23 cents for each dollar invested and it is estimated that the company will be able to recover the investment in 1 year, 3 months and 3 days from its implementation, in addition, the project can withstand a decrease in revenue of up to 26.30% without affecting its profitability, and an increase in costs of up to 32.40%, however, if these rates are exceeded, the project becomes sensitive to changes.